Insilico STUDIES ON ANTIMICROBIAL PEPTIDES (AMPs) FROM Calliphora vicina, THE BLOW FLY OF FORENSIC IMPORTANCE (Applied Biological Research, 2023)
The forensic flies colonize and feed on carcasses and cadavers and draw  their nourishment from the dead and decomposed matter. They find  significance in forensic studies as nutrient recyclers, disease vector and  reveal association with pathogenic microorganisms. Despite their  importance in forensistudies, their innate immune defense molecules like  antimicrobial peptides (AMPs), have not been well characterized.  Therefore, we characterized the AMPs from forensic fly, Calliphora vicina.  using MSA, NCBI Tree Viewer, I-TASSER, Peptide cutter, NetPhos 3.1, Prot param Expasy insilico tools, for prediction of homology and  evolutionary relationships, structure, function, potential cleavage,  phosphorylation sites and physicochemical properties. We report for the  first time thdifferences in the structures of C. vicina AMPs and the  presence of nucleic acid-binding domain in Cecropin, at aspartic acid  (D19), glutamine (Q15), histidine (H16) probably contributing to the  antiviral immune responses. This in-silico study highlights the diversity of  AMPs in forensic flies and reveals their indepth structural information. Further, these AMPs partially explain their association with pathogenic  microorganisms.
Keywords: Antimicrobial peptide; Calliphora vicina; cecropin